Factors affecting financial planning among young employees / Aishah Abu Samah - Abu Samah, Aishah (Faculty of Business and Management, 2015)
Financial planning advice is becoming a mandatory for all Malaysians. This is to ensure that they have a better standard of living presently, or in future. Having a adequate education about financials management is important as it able the employees to know, monitor, and effectively use financial resources to enhance the well-being and economic security of an individual, his family, and their business. So to be financially literate becomes important from the initial stages of one’s career. But due to some personal or professional hindrances they become financially illiterate. This paper examines about three factors that might affect the financial planning among young employees. The three factors are attitude, commitment and personal income. Result of this study indicates that attitude plays a very crucial role to employees to do financial planning. Attitude is reflecting how employees aware and act regarding to manage their money. Credit cards, car loans and study loan are the example that Malaysians have to pay.